Synthetic spectra of BeH, BeD and BeT for emission modeling in JET plasmas. (24th August 2018) - Darby-Lewis, D; Tennyson, J; Lawson, K D; Yurchenko, S N; Stamp, M F; Shaw, A; Brezinsek, S
Abstract: A theoretical model for isotopologues of beryllium monohydride, BeH, BeD and BeT, A 2 Π to X 2 Σ + visible and X 2 Σ + to X 2 Σ + infrared rovibronic spectra is presented. The MARVEL procedure is used to compute empirical rovibronic energy levels for BeH, BeD and BeT, using experimental transition data for the X 2 Σ +, A 2 Π, and C 2 Σ + states. The energy levels from these calculations are then used in the program Duo to produce a potential energy curve for the ground state, X 2 Σ, and to fit an improved potential energy curve for the first excited state, A 2 Π, including a spin–orbit coupling term, a Λ-doubling state to state (A–X states) coupling term, and Born–Oppenheimer breakdown terms for both curves. These, along with a previously computed ab initio dipole curve for the X and A states are used to generate vibrational-rotational wavefunctions, transition energies and A-values. From the transition energies and Einstein coefficients, accurate assigned synthetic spectra for BeH and its isotopologues are obtained at given rotational and vibrational temperatures. The BeH spectrum is compared with a high resolution hollow-cathode lamp spectrum and the BeD spectrum with high resolution spectra from JET giving effective vibrational and rotational temperatures. Full A–X and X–X line lists are given for BeH, BeD and BeT and provided as supplementary data on the ExoMol website.